A study of time use, learner autonomy and academic achievement among secondary school students in Malaysia / Razimi Zakaria, Ng Siew Foen and Lai See May - Zakaria, Razimi; Ng, Siew Foen; Lai, See May (Research Management Institute (RMI), 2013)
The preliminary report of the Malaysian Education Blueprint - 2013-2025 (Malaysia Ministry of Education, 2012) highlights the importance, in a globalized world, of producing future intellectual, social and human capital for Malaysia. It is paramount to note that adolescents are the future human capital of Malaysia. Literature indicates adolescents are confronted with an environment that is rapidly changing and the time spent on non-school-related activities has negatively impacted academic performance. This research investigated the contribution of time use among students to academic achievement. The sample of secondary school students was stratified to ensure balance of gender, school type and grade level. Correlation analyses were conducted to determine the associations among the variables identified in the study. Participants completed the Daily Record of How I Use My Time each day for seven consecutive days. Cooperating schools provided copies of the academic transcript of each participant. This information was used to establish the overall secondary school academic achievement of each participant. The data collected were subjected to bivariate comparisons of means and t-test comparisons of means to yield correlations among the target variables. The findings of this research support those of some previous studies and contradict those of other studies, many conducted with non-Malaysian populations. In sum, the present study may help to develop a conceptual framework for guiding efforts to improve academic performance, as it relates to time-use, as a contribution to accomplishing the national agenda of Malaysia.